The Influence of Intellectual Capital and Shariah Compliance on Social Performance (Study Empirical on Islamic Banks in 2018-2020) - Vienka Ferenzha Salsabilla; Umi Solikhah; Fyna Maulina; Depriska Lailatul Aroof; Ufi Anjani; Bima Cinintya Pratama (UM Purwokerto Press, 2022)
The purpose of this study was to determine the effect of Intellectual Capital and Shariah Compliance on Social Performance. The sample of this research is in the form of financial statements of Islamic banks on The Financial Services Authority for the period 2018 - 2020 for 3 years. The sampling technique used is purposive sampling technique so that a sample of 13 companies is obtained that has met the criteria. The data analysis technique used is multiple regression with the help of the SPSS program. The results of this study indicate that Intellectual Capital and Shariah Compliance have no partial effect on social performance.